Environment Matters at the World Bank, 2007 Annual Review : Climate Change and Adaptation - World Bank (Washington, DC, 2013)
This edition of environment matters arrives just as the international community embarks on a two-year process to secure a new global framework to limit the amounts of greenhouse gases (GHGs) entering the atmosphere and devise ways to help developing countries adapt to and prepare themselves for the effects of climate change. At the World Bank, the author believe that climate change, and developing countries' adaptation to it, is a critical challenge of our time that must be integrated into core development strategies. Changes in temperatures and weather patterns will affect the frequency and severity of rainfall, droughts, floods, and access to water, flood protection, health, and the use of land. These impacts will not be evenly distributed. The poorest countries and people, those least responsible for climate change and least able to cope with it, will suffer earliest and most due to their geographical location, low incomes, and low institutional capacity, as well as their greater reliance on climate-sensitive sectors like agriculture. This is why building up resilience to increasing climate variability is the most significant climate challenge facing many developing countries. But we believe that adaptation, while necessary in and of itself, can also serve to meet the development objectives of countries. Many appropriate adaptive measures are consistent with good development practice. They can improve the local environment, increase resilience to current and future climate variability and to natural disasters, and ease the dissemination of innovative technologies. They can also reduce resource scarcity within specific social groups or regions, thereby addressing some of the principal causes of social unrest and violent strife. In other words, climate action is development action.